TRIASSIC MORB MAGMATISM IN THE SOUTHERN MIRDITA ZONE (ALBANIA) - Bortolotti, Valerio; Chiari, Marco; Kodra, Alaudin; Marcucci, Marta; Marroni, Michele; Mustafa, Faruk; Prela, Mensi; Pandolfi, Luca; Principi, Gianfranco; Saccani, Emilio (Ofioliti, 2006)
In southern Albania the Mirdita Ophiolitic nappe is characterized by subophiolitic complexes in which remnants of volcanic ophiolite sequences of Triassic age have been identified, either as rare blocks of variable dimension in the Rubik Complex, or as a thin tectonic unit (the Porava Unit), sited immediately under the main ophiolitic masses of the Eastern Ophiolite Belt. In this paper the results of petrological investigations on basalts and biostratigraphical studies on associated radiolarian cherts included in these subophiolitic complexes units are presented.Biostratigraphical investigations indicate that cherts have ages ranging from Middle to Late Triassic. The associated basalts are represented by both high- Ti mid-ocean ridge basalts (MORB) and alkaline ocean island basalts (OIB). MORB rocks mainly consist of basalts and ferrobasalts with a mild enrichment in low field strength elements and flat rare earth element patterns and, subordinately, by basalts strongly depleted in incompatible elements and light rare earth elements. The chemistry of slightly enriched MORB is consistent with a generation in a mid-ocean ridge setting, from somewhat enriched sub-oceanic mantle source(s), whereas depleted MORB generated from a primitive MOR-type mantle source. The OIB rocks imply a generation in a within-plate oceanic setting from a mantle source enriched by plume chemical components.Basalts and associated cherts from southern Albania subophiolitic mélanges represent remnants of a Triassic oceanic lithosphere, which testify for the existence, from northern Albania to southern Greece, of a Middle to Late Triassic oceanic basin located between the Adria and Eurasia plates.The occurrence in the Rubik Complex and Porava Unit of MOR basalts generated from differently enriched sources, as well as of alkaline OIBs, suggests that the early stage of oceanic spreading was variably associated with a plume activity.